PENGARUH DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH PEMERINTAH KABUPATEN DAN KOTA DI JAWA TIMUR - Poppy Eliza Ritmadanti Jatmiko (Jurnal Ekonomi Pembangunan, 2016)
The purpose of this research is to determine the influence of equalization funds and local own-source revenues to district and city Government expenditure of East Java. The analysis tool used is regression panel data, regression estimation method selected is using Fixed Effect method. The results of analysis stated that the two variables, namely the equalization fund and local revenue positive effect on district and city Government expenditure of East Java. Although the fund balance positive influence on shopping areas, but cause a regional equalization funds can not be independent, since they rely on the central government. Whereas in the autonomous regions, each region are urged to maximize local revenue for local revenue is a reflection of the independence of a region. The higher contribution of the local revenue of the local revenue, the level of independence of a region is getting higher and higher contributions fund the balance of the local revenue, the level of independence of a region lower, which means dependence on the central government area is high.